Navigator based respiratory gating during acquisition and preparation phases for proton liver spectroscopy at 3 T. (13th January 2014) - Hock, A.; Valkovič, L.; Geier, A.; Kuntzen, T.; Boesiger, P.; Henning, A.
<x xml:space="preserve">Abstract</x> Proton magnetic resonance spectroscopy (1H MRS) enables the non‐invasive investigation of the human liver; however, because of technical difficulties it is not regularly used for diagnosis of liver diseases in clinical routine. Breathing motion is one of the major challenges, as it decreases spectral quality and leads to misplacement of the spectroscopic voxel. To overcome this problem, real‐time navigator gating for spectral acquisition and preparation steps (B0 shimming, water frequency determination, receiver gain optimization, and water suppression) combined with short TE, optimized first order projection based B0 shimming, water suppression, and inner‐volume saturated point resolved spectroscopy (PRESS) at 3 T is suggested. Simultaneous lipid and trimethylamine quantification is demonstrated by means of phantom, volunteer, and representative patient measurements. Precise localization of the voxel despite respiratory motion, increased spectral quality (higher signal‐to‐noise ratio and reduced linewidth) compared with measurements without respiratory gating, and the possibility of acquiring data without additional subject instructions regarding breathing enable robust and accurate liver 1H MRS measurements with this novel acquisition protocol. Copyright © 2014 John Wiley & Sons, Ltd.